Teachers’ General Pedagogical Knowledge and self-efficacy On STEM Instructional Practices On Primary Teacher - Ghozali Rusyid Affandi; Mohammad Faizal Amir; Widyastuti Widyastuti (JETL (Journal of Education, Teaching and Learning), 2022)
Not only cognitive knowledge, but also modern 21st-century instructional practices employed by primary school teachers are crucial for equipping students with a well-rounded education. But also to prepare students with the motivation, knowledge, and skills in science, technology, engineering, and mathematics (STEM) required for the digital age workforce. This study aims to determine the efficacy of STEM instructional practice training in enhancing primary school teachers' general pedagogical knowledge and self-efficacy. Forty-six primary school teachers from Sidoarjo, East Java, participated in the study. The experimental group (n=23) and the control group (n=23) comprised a total of 46 individuals. In the experimental group, participants received instruction in STEM-based mathematics learning planning. A questionnaire is used to assess teachers' general pedagogical knowledge and self-efficacy in STEM instructional practice before and after training. The study on teachers' general pedagogical knowledge revealed that, after training, the experimental group achieved better results than the control group. In the experimental group, the average score for the instructional process aspect increased to 9.5 points. The average value of the learning process aspect has increased by 15,5 points, while the average value of the assessment aspect has increased by 5,5 points. After receiving training, teachers in the experimental group demonstrated greater self-efficacy than their counterparts in the control group. The findings can be utilized by primary school teachers to enhance their STEM-related general pedagogical knowledge and self-efficacy.